2021
DOI: 10.1007/s10967-021-07980-w
|View full text |Cite
|
Sign up to set email alerts
|

Technical and radiological characterisation of fly ash and bottom ash from thermal power plant

Abstract: Huge quantities of fly ash and bottom ash are generated from thermal power plants and it presents great concern for country, mainly due to the environmental effects. In this study, fly ashes and bottom ash were characterized from technical and radiological aspects. Health effect due to the activity of radionuclides 226Ra, 232Th and 40K was estimated via radium equivalent activity (Raeq), external hazards index (Hex), the external absorbed dose rate (D) and annual effective dose rate (EDR). The specific surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The unburned carbon content was also measured with the loss on ignition (LOI), for which 22.81%, 16.65%, and 30.62% were obtained (see Table 1) for CFC 1, CFC 2, and CFC 3 respectively. Similar results have been reported by other authors (27,29), which is attributed to proportions of unburned coal; where the latter has been reported with high levels of PHA (13). Concerning toxicity, it has been found that one of the most frequent occupational risks is the risk of contracting cancer due to exposure to byproducts of coal combustion, due to the content of PHA and radioactive natural radionuclides, either by ingestion or dermal contact (4,37).…”
Section: Chemical and Elemental Compositionsupporting
confidence: 87%
See 1 more Smart Citation
“…The unburned carbon content was also measured with the loss on ignition (LOI), for which 22.81%, 16.65%, and 30.62% were obtained (see Table 1) for CFC 1, CFC 2, and CFC 3 respectively. Similar results have been reported by other authors (27,29), which is attributed to proportions of unburned coal; where the latter has been reported with high levels of PHA (13). Concerning toxicity, it has been found that one of the most frequent occupational risks is the risk of contracting cancer due to exposure to byproducts of coal combustion, due to the content of PHA and radioactive natural radionuclides, either by ingestion or dermal contact (4,37).…”
Section: Chemical and Elemental Compositionsupporting
confidence: 87%
“…The chemical composition of the ashes of the study is presented in (15,27,(30)(31)(32)(33). Some authors mention that coal ash from brick manufacturing is extremely toxic to human health and that cancer can be contracted from exposure to elements such as chromium (34).…”
Section: Chemical and Elemental Compositionmentioning
confidence: 99%
“…FAs are mainly composed of SiO 2 , Al 2 O 3 , and Fe 2 O 3 , with CaO content below 10% in ASTM F-type ashes [ 30 ], which are the ones mainly used in this study. Likewise, the percentages of MgO and TiO 2 are very low in this type of ash [ 78 ]. The content in the naturally occurring radioactive uranium and thorium series would be related to the coal used in the power plant [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…As compared to fly ash, bottom ash is collected at the bottom of the boiler and has coarser, angular, large-sized particles with a greater content of unburned carbon [ 102 ]. Figure 8 shows the SEM image of bottom ash which has coarser, irregular large-sized angular particles.…”
Section: Resultsmentioning
confidence: 99%